Beberapa Catatan tentang Peradilan Tata Usaha Negara di Indonesia - Ridwan HR (Fakultas Hukum Universitas Islam Indonesia, 2002)
Institution as the human product is not steril from tpe various factors like politics, economy, culture and soforth, including the Acts number. 5,1986 aboutjun'stiction of State Procedure, therefore the Acts innovation is surely needed towards the better condition, just and relevance to the society development. This article is aimed as athinking contribution in the frame ofinnovation for the Acfs number. 5, 1986 by restricting for the three points including the problem existing sorrounding it namely material and the reason of accusation, the meaningof board or official of state procedure as the accused and realization of decision.